Analysis of antibacterial and antioxidant potential of commercial essential oils from Tuzla markets - HoroziÄ‡, Emir; ImamoviÄ‡, Merima; BjeliÄ‡, Edita; SalkoviÄ‡, Vedad; KariÄ‡, Enida; HusejnagiÄ‡, Darja; AhmetoviÄ‡, Nihada (International Journal of Advanced Chemistry, 2022)
Essential oils are natural products that contain a wide range of biologically active organic compounds. Therefore, they are intensively researched as potential antioxidant, antimicrobial and antitumor preparations, which could to some extent replace the classic synthetic drugs used to treat various pathological conditions. In this paper, the antioxidant and antibacterial activity of selected essential oils available in local markets in the area of Tuzla was examined. The efficiency of neutralization of free radicals was determined by spectrophotometric method, while the antibacterial potential was determined by diffusion technique on reference bacterial strains. For essential oils that showed antibacterial activity, the minimum inhibitory concentration (MIC) was determined using a dilution technique. The results showed that commercial essential oils have a high ability to neutralize DPPH radicals in vitro. The diffusion technique confirmed the high antibacterial activity for the essential oils of tea tree, eucalyptus, immortelle and wormwood, while the essential oils of lemon and cedar showed extremely weak antibacterial activity.Â Â